A computational analysis of the binding free energies of apoptosis signal-regulating kinase 1 inhibitors from different chemotypes. Issue 18 (12th December 2021) - Volynets, Galyna P.; Pletnova, Larysa V.; Sapelkin, Vladislav M.; Savytskyi, Oleksandr V.; Yarmoluk, Sergiy M.
ABSTRACT: Apoptosis signal-regulating kinase 1 (ASK1) has recently emerged as an attractive molecular target for pharmaceutical intervention. Several classes of small-molecular ASK1 inhibitors have been identified. In this article, we analysed the binding of small-molecular inhibitors from different chemotypes with ASK1 using molecular dynamic simulations. The umbrella sampling technique was used to calculate the binding free energy (ΔG) for these compounds with ASK1 ATP-binding pocket. According to the obtained results, umbrella sampling gave correct ranking of the binding affinities for investigated inhibitors relative to their experimental pIC50 values and can be useful for further structure-based design of ASK1 inhibitors to accelerate lead optimisation. Trial registration: ClinicalTrials.gov identifier: NCT02466516. .